Study on the spatial distribution characteristics of urban innovation power in Yangtze River Delta urban agglomeration. Issue 5 (April 2020) - Liu, Jing; Dou, Yitao; Lu, Yanwen; Yang, Li
Abstract: Based on the evaluation index panel data of innovation capacity of 26 cities in the Yangtze River Delta urban agglomeration from 2013 to 2017, the global entropy method and exploratory spatial data analysis method (ESDA) were used to evaluate and analyze the spatial characteristics of urban innovation capacity. The results show that: (1) From 2013 to 2017, the innovation capacity of the Yangtze River Delta urban agglomeration has an obvious regional difference, showing a distribution pattern of "Strong In The East And Weak In The West" on the whole. (2) From 2013 to 2017, the innovation capacity of the Yangtze River Delta urban agglomeration shows significant positive agglomeration characteristics in space. (3) The spatial agglomeration evolution of the innovation capacity of each city has obvious spatial locking characteristics. Based on the research conclusion, this paper puts forward some suggestions on strengthening urban innovation connection, improving innovation structure, increasing innovation investment and strengthening scientific and technological strength.